TRIZ and Design Thinking methodologies integration at the beginning of the product development process in the personal health equipment sector. - Uribe Ocampo, Jovany (2022)
Different authors identify and address the difficulties encountered in the early stages of the Product Development Process (PDP), referred to in the literature as Fuzzy Front End (FFE). Likewise, scholars indicate how the FFE has a decisive impact on the future product, the impact being more pronounced in the context of High Degree of Innovation (HDI). At the same time, the FFE phase is the most critical phase of the PDP due to the difficulty of understanding and articulating the opportunities detected. However, the literature on FFE in the context of HDI lacks functional and practical proposals. On the other hand, an effort is found in academia for the incorporation of good engineering practices in the Personal Health Equipment (PHE) sector, due to the confluence of economic and social factors in this sector. PHE products are highly regulated due to the inherent risks to users. In addition, development is considered complex and dynamic, both from a user and technology perspective. Thus, the objective of this research was to synthesize, through literature research, the conception of an FFE model for the PHE sector of the large mechanical-electronic area specific to develop products with a high degree of innovation and realized through the integration of TRIZ methodologies, which has an emphasis on technological evolution, and Design Thinking (DT), which has a user-centered approach. The proposed model was then validated with four practical applications in companies of the PHE sector. The validation allowed to determine how this model in the context of HDI, supports the clarification of the problem and the search for innovative solutions, both from the user\'s and the technology\'s point of view. The results obtained were: an FFE model, specific for industrial companies in the area of large mechanics and electronics of the PHE sector, balanced between the procedural - descriptive, and the performative - prescriptive, through the insertion of methodologies and, finally, of techniques that guide and support the process and its critical activities. Thus, it was observed that the practical application of the model allowed to support the development of products in their initial phase with a high degree of innovation from the user\'s point of view and also from the technological point of view.